Smart electronic applications with Google home - K A Abdul Hameed (Nanyang Technological University, 2024)
The Internet of Things (IoT) has revolutionized various aspects of daily life, with smart home technology emerging as a prominent application. Smart homes integrate IoT devices and sensors to automate and control various household functions, enhancing convenience, comfort, and security for inhabitants. However, despite the advancements in smart home technology, there are notable shortcomings in energy monitoring and cost efficiency. Existing systems often lack granular insights into energy consumption patterns and struggle to offer actionable strategies for optimizing energy usage, leading to suboptimal resource utilization and increased utility expenses. This project aims to address these shortcomings by leveraging IoT in smart home technology to monitor energy usage and propose more efficient methods. Utilizing a Raspberry Pi as the central processing units, along with NodeRed for programming, data collected from various sensors will be stored in a MySQL database for analysis. The project incorporates facial recognition technology for enhanced security, a rain sensor to detect weather conditions and automate tasks like bringing in clothes and employs machine learning algorithms to analyse energy consumption data and suggest energy-efficient practices. By integrating these technologies, the project endeavours to enhance the sustainability and efficiency of smart homes, contributing towards a more environmentally conscious and cost-effective lifestyle.